1995
DOI: 10.1007/bf02635666
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability ofThevetia peruviana juss seed oil

Abstract: Thevetia peruviana seed showed characteristic changes in physicochemical properties when heated at 180, 200, and 220°C over a period of 15 h. There is no striking significant difference in the five parameters (iodine value, acid value, peroxide value, saponification value, and polar compounds) studied for the three working temperatures. Thevetia seed oil showed good thermal stability and will be a good frying and cooking oil. JAOCS 72, 745-747 (1995).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Recent research by Ibiyemi et al (1995) revealed that T. peruviana has superior oils in terms of quality and quantity than J. Curcas. The seed contains 60 -65% oil and the cake comprise of 30 -37% protein.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research by Ibiyemi et al (1995) revealed that T. peruviana has superior oils in terms of quality and quantity than J. Curcas. The seed contains 60 -65% oil and the cake comprise of 30 -37% protein.…”
Section: Introductionmentioning
confidence: 99%